A review of honey supplementation on endurance performance in athletes - Chee Ping Wong (Scientific Research and Community Ltd, 2020)
Nutritional ergogenic aids are substances which can enhance athletic performance by influencing physiological processes. Sportspersons usually take supplements before, during and after a sports competition to make sure they have adequate nutrition, maximize their energy storage and enhance their physical sports performance. Endurance athletes such as marathon runners, triathlons and cyclist are known to use supplements to enhance their physical performance. Supplements may enhance endurance performance by increasing the available blood glucose during exercise, increasing body glycogen storage in muscle and liver, and increasing antioxidant status. The increasing availability of adenosine triphosphate (ATP) in the working muscles will augment physical sports performance. It is believed that honey is an ergogenic aid supplement but it is lacking in solid scientific evidences to prove its efficacy. Thus, it has received scientists’ attention to conduct scientific research to test this supposition. This article discusses the effects of honey supplementation on endurance performance in athletes.